Maitre Pan Lubricant Market Penetration Strategy in Eastern Australia - Permana, Sidi Sidik; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2012)
MAITRE PAN Lubricant is the subsidiary of PT.MAITRE PAN, manufacturing and distributing high-quality lubricant to both the automotive and industrial customers. Over the years, MAITRE PAN Lubricant have expanded their business, exporting their product to other country such as Japan, China, and many other. In 2009, MAITRE PAN Lubricant enters the Australian market by exporting their product using country distributor called the Indolubricant. Facing many challenges from the market, MAITRE PAN Lubricant is now looking to penetrate the Australian market by focusing on the eastern region of Australia, finding the right market penetration strategy is the key to MAITRE PAN Lubricant’s success.The market penetration strategy can be used to increase sales of the company’s existing product in the existing market, the increase of sales can be done by increasing the customer’s purchase, increase the customer’s volume of use of the product, or finding new uses for the existing product.In order to know which strategy that can be recommended for MAITRE PAN Lubricant, we will analyze the market attractiveness of Eastern Australia and the competitive advantage of MAITRE PAN Lubricant, we will also see the macro condition factor of Australia that will affect the lubricant business, the purpose of the analysis is to find the strength, weakness, opportunities and challenge of MAITRE PAN Lubricant in the market. The method that we are going to use is literature study, in-depth interview, and acquiring and analyzing secondary data.The result of the analysis will show us that there is a potential opportunity in the Eastern Australia’s mining and agricultural industry segment for lubricant; this is due to the growth of both of those industries. The recommended strategy to approach the segments is the flanking and guerilla strategy.The flanking strategies are including the development of new product, lobbying, and adding new distribution channel, guerilla strategies are customer relationship management, website improvement, and marketing program initiative. Each of those strategies has their own implementation steps and the implementation time’s estimation is one year starting from July 2012. Keywords: market penetration, lubricant flanking, guerilla